0705 Short Sleep Duration is Associated with Lower Stress-Induced Blood Pressure Reactivity in Young Women with Early-Onset Myocardial Infarction, But Not Men. (27th April 2018) - Bromfield, S G; Hardy, S; Sullivan, S; Hammadah, M; Shah, A; Levantsevych, O; Kaseer, B; Elon, L; Li, L; Bremner, J D; Quyyumi, A; Vaccarino, V; et al.
Abstract: Introduction: Short sleep duration has been linked to elevated blood pressure (BP) and incident hypertension. These associations are more pronounced among women, for reasons that remain unknown. Gender differences in BP responses to emotional stress may play a role. Thus, we hypothesized that: women, but not men, with short sleep duration would have dysregulated BP reactivity to acute mental stress. Methods: Participants were from the Myocardial Infarction (MI) and Mental Stress 2 (MIMS2) study (N=293). Sleep duration was assessed via self-report and defined as short if <5 hours. Systolic BP (SBP) and diastolic BP (DBP) were measured at rest and during a mental stress test (speech task). Gender stratified linear regression models were performed to examine the association between short sleep and BP reactivity, adjusting for sociodemographic factors, disease severity, medications and depression. Results: Of the 293 post-MI participants included in this analysis (50% women, mean age 51 years), 49 (17%) reported short sleep duration. The mean change in BP reactivity to acute mental stress was 41 mmHg (standard deviation [SD], 16) for SBP and 29 mmHg (SD, 11) for DBP. Among women, both SBP and DBP reactivity were lower in those with vs. without short sleep (Beta: -7.66, p = 0.04; Beta: -5.89, p = 0.03 respectively), after multivariable adjustment. There were no significant associations observed between short sleep duration and SBP (Beta: -0.20, p = 0.97) or DBP (Beta: -3.18, p = 0.33) reactivity among men. Conclusion: Short sleep duration is associated with blunted SBP and DBP reactivity to acute stress in women post-MI, but not men. The impact of short sleep and its impact on BP reactivity on long term cardiovascular outcomes among women with coronary artery disease should be further evaluated. Support (If Any): None.